1999
DOI: 10.1046/j.1365-3016.1999.00189.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and child constitutional factors and the frequency of melanocytic naevi in children

Abstract: This study examined the association between numbers of benign melanocytic naevi in 7-year-old children in Oxfordshire born in 1988-9 with their mother's arm naevus count, and maternal and child pigmentation factors. We believe this is the first time that the relationship between child and maternal naevus counts has been reported. A high naevus count in the child was associated with male sex (P = 0.009), freckling (P = 0.001) and propensity of the child to burn in the sun (P = 0.05). A low naevus count was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
11
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 23 publications
8
11
0
Order By: Relevance
“…Most researchers 7,13,21,[30][31][32] have found a higher number and density of MN in boys compared with girls, and we found the same tendency in our study. Boys aged 9 to 10 years had more MN of all sizes compared with girls, while male adolescents aged 14 to 15 years had more MN, both of all sizes and MN 2 mm of larger.…”
Section: Commentsupporting
confidence: 90%
See 2 more Smart Citations
“…Most researchers 7,13,21,[30][31][32] have found a higher number and density of MN in boys compared with girls, and we found the same tendency in our study. Boys aged 9 to 10 years had more MN of all sizes compared with girls, while male adolescents aged 14 to 15 years had more MN, both of all sizes and MN 2 mm of larger.…”
Section: Commentsupporting
confidence: 90%
“…[8][9][10]21,35 Some studies showed that the prevalence of MN among white children decreased with the increase in skin pigmentation, 8,10,30,31 although other studies did not confirm this relationship either. 13,22,23 Our study did not show any relationship between the skin type (light, medium, or dark) and the number of MN. These conflicting results could have been caused by a subjective evaluation of the skin color.…”
Section: Commentmentioning
confidence: 46%
See 1 more Smart Citation
“…Recent studies point to genetic-environmental interaction as a plausible explanation for the origin of melanocytic nevi. Clustering of nevi in families 26 and higher concordance rate of nevus counts between homozygotic compared to dyzygotic twins have been documented. 27 Most children are born without nevi and develop them later in life.…”
Section: Resultsmentioning
confidence: 98%
“…Studies on parental pigmentary factors have shown MN counts of children to be correlated significantly with MN counts of mothers 34 and the arms of both parents. 19 The present longitudinal data support this association.…”
Section: Discussionmentioning
confidence: 99%